PROYECTO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA EMPRESA PRODUCTORA Y COMERCIALIZADORA DE HARINA DE CAMOTE EN EL CANTÓN CATAMAYO PROVINCIA DE LOJA - Caamaño Romero, Mariuxi Katherine (2016)
The present research was developed in the Canton of Catamayo, Loja province, based on the need to use resources available locally and some factors that were conducive to raise the project called "PROJECT FEASIBILITY FOR IMPLEMENTATION A producer and marketer POTATO FLOUR IN THE CANTON CATAMAYO " Therefore objectives that must be met with the development of this work as are the following arises: Determine the feasibility of the project to launch, through market research, technical, administrative, financial and finally study with a financial assessment to determine the profitability of the project. As part of the study concerning theoretical generalities, types and processes, production, planting sweet potatoes and other concepts framed the process of this project is presented. For the project was taken as basis methods and techniques that allow identification of the Catamayo Canton population, thanks to that gathering information was obtained by conducting surveys; and then continue to develop research work, in order to measure the level of feasibility for the creation of the company. Within the market study two types of claims are considered: the potential or the total demand of 97.90% with a total of 8039 households consuming flour and effective demand of 69.44% ie 5582 families who are willing to acquire the product. On the supply side 40 surveys were applied to shops and commercial premises which sells basic necessities. Upon completion of market research, we proceeded to develop the technical study in which the size of the plant in relation presents installed capacity is 312,000 pounds a year and used 104,000 pounds of sweet potato flour a year, 6 the macro and micro location was reflected, the respective programs process flow for the production and marketing of the product. Within the organizational study it found that the company will be legally incorporated as a Limited Company, will have a minimum duration period of 5 years and as its name business name will be "Flours Don Teo'" Cia. Ltda. As was determined organizational structures, in which the hierarchical levels of the company is identified, it was concluded with the specification manuals have clear functions and set the functions of personnel working within the company. In the financial study to consider the items in the project by fixed, deferred and current assets it indicated; to calculate the total investment of it, to proceed to determine the funding for this. Respectively the overall budget costs, costs and revenues, fixed and variable costs, breakeven point where the level of production to remain at a point where not miss is determined, was obtained but neither won, for the first year we have in relation to sales 36848.00 production capacity and 48.13%; in the profit and loss for the first year we have earnings of $ 13.053,44 and cash flow of $ 18.993,28. Finally, it was concluded with the financial evaluation where we calculate whether the project is feasible or not; based on the following economic indicators: Van with $ 46,150,05, with a 32.82% IRR the project to be profitable since the rate is much higher in relation to the lending rate of the bank, Capital Recovery Period it is one year seven months and sixteen days, Benefit cost ratio is 1.40, therefore, that for every dollar invested 0.40 cents and Sensitivity Analysis will gain the increased costs will support changes of 21.36% and declining revenues 15.26%. These indicators allow us to measure whether the project is feasible or not, giving us positive, each of the indicators which ensure that this project can be done without much difficulty. At the end of this paper the conclusions and recommendations specified therein and in turn are attached annexes and bibliography thereof.